Kontribusi satwa dalam menunjang ketahanan pangan masyarakat Distrik Tembuni Kabupaten Teluk Bintuni - Iriansul Iriansul; Irba A. Warsono; M. Jen Wajo (Program Pascasarjana Universitas Papua, 2018)
The biodiversity of wild animals in the Tembuni District has the potential of fulfilling nutrition and the economy for the community, but the condition of the area which is still constrained by limited access and still using traditional hunting techniques which influences the level of public consumption of wild animal. This condition has an influence on the pattern of consumption and food security, most of the people of the world. This study aims to identify the description of the region, the characteristics of the population and the potential of hunted animals used by the 4 villages in Tembuni District, namely Bangun Mulya, Mogoi Baru, Tembuni and Araisum villages, so that it can be seen a general description of the area, hunting patterns and techniques 4 villages. It is recognized that the problem of meeting the needs of animal food is used as a policy direction and solution so that it can become information related to the level of consumption of animals but still prioritizes sustainable use to increase the added value of hunting resources and realize food security from animals.